The evolution of the East Asian currency baskets: still undisclosed and changing - Gunther Schnabl (Center for Economic Studies and ifo Institute (CESifo), 2006)
Both before and after the Asian crisis, the dollar has been the dominant anchor and reserve currency in East Asia. Due to underdeveloped capital markets and the limited international role of their domestic currencies, the East Asian countries (except Japan) are likely to continue to stabilize exchange rates and to accumulate international reserves. Yet expectations of further dollar depreciation may trigger a re-orientation of exchange rate policies based on basket strategies. Rolling econometric estimations of the basket structures in East Asia suggest growing weights for the Japanese yen in most East Asian currency baskets. The role of the euro as a reserve currency in East Asia remains uncertain.
Keywords: F31; G15; E58; 330